Edukasi Tanaman Obat Keluarga Bersama Sehat Terjamin (TOGA BERSALIN) diKampung Botol Bengkulu - Masita, Era; Oktarina, Seri; Marete, Riste; Simangusong, Epipanias; Juita, Elva; Yunita, Euis Endah; Situmorang, Ronalen Br.; Pebriani, Emi; Susanti, Meri Epriana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Family Medicinal Plants (TOGA) are easy-to-apply household health resources that play an important role in promotive and preventive efforts, particularly for elderly individuals who are vulnerable to degenerative diseases. In Kampung Botol RT 05, the community owns home yards and several medicinal plants, but their use remains limited due to a lack of knowledge regarding plant types, health benefits, and processing methods. The TOGA BERSALIN program (Family Medicinal Plants Bersama Sehat Terjamin) is an educational innovation aimed at improving community understanding.